2015
DOI: 10.1080/13102818.2015.1018839
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and allelic variation of two novel catalase genes (SoCAT-1andSsCAT-1) inSaccharum officinarumL. andSaccharum spontaneumL.

Abstract: (2015) Cloning and allelic variation of two novel catalase genes (SoCAT-1 and SsCAT-1) in Saccharumofficinarum L. and Saccharumspontaneum L., Biotechnology & Biotechnological Equipment, 29:3, 431-440, DOI: 10.1080/13102818.2015 Catalases (CAT) play important roles in plant defence mechanisms, stress response, cellular redox balance and aging delay. In order to clone CAT genes in cultivated (Saccharum officinarum L.) and wild (S. spontaneum L.) sugarcane, we designed two pairs of specific primers using a full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…The protein sequence of CsCAT3 was aligned with the template protein 4qol.1.A from amino acid 17-448 with a coverage of 95%. As shown in Figure 2, the predicted structure of CsCAT3 could be conceptually divided into four subunits, which is in accordance with a pervious study [14]. In addition, The CsCAT3 protein and template protein shared a high degree of homology (49.04%), and the GMQE value and QMEAN Z-Score were 0.77 and ¡1.08, respectively, suggesting a high reliability of the predicted structure ( Figure 2).…”
Section: Cloning and Characterization Of Cscat3 Genesupporting
confidence: 59%
See 1 more Smart Citation
“…The protein sequence of CsCAT3 was aligned with the template protein 4qol.1.A from amino acid 17-448 with a coverage of 95%. As shown in Figure 2, the predicted structure of CsCAT3 could be conceptually divided into four subunits, which is in accordance with a pervious study [14]. In addition, The CsCAT3 protein and template protein shared a high degree of homology (49.04%), and the GMQE value and QMEAN Z-Score were 0.77 and ¡1.08, respectively, suggesting a high reliability of the predicted structure ( Figure 2).…”
Section: Cloning and Characterization Of Cscat3 Genesupporting
confidence: 59%
“…Genomewide studies have demonstrated that CAT is encoded by a small gene family which has been reported in many plant species, including Nicotiana plumbaginifolia [4], Hordeum vulgare [5], Zea mays [6], Arabidopsis thaliana [7,8], Solanum lycopersicum [9], Capsicum annuum [10], Oryza sativa [11,12], Saccharum officinarum [13,14 ], and Cucumis sativus [15].…”
Section: Introductionmentioning
confidence: 99%
“…Catalase (H 2 O 2 /H 2 O 2 oxidoreductase, EC 1.11.1.6; CAT) is a tetrameric, heme-containing enzyme that catalyzes the dismutation of H 2 O 2 into H 2 O and O 2 and plays important role not only in plant metabolism and defense but also in signal perception (Loew 1901;Redinbaugh et al 1990;Scandalios et al 1997;Mhamdi et al 2010;Hu et al 2010;Nie et al 2015;Liu et al 2015). Historically, the degradation of H 2 O 2 in plant and animal tissues was first observed by Thenard in 1881; whereas, Loew (1901) proved that a new enzyme, which he named Bcatalase,ŵ as responsible for the degradation of H 2 O 2 in tissues (Aebi and Sutter 1971).…”
Section: Catalase Localization and Biochemical Characterizationmentioning
confidence: 99%
“…Regarding CAT genes and isoforms, CATs can exist in multiple molecular forms or isozymes encoded by multiple genes (Scandalios 1968). Notably, unlike animals which contain a single CAT gene, all angiosperm/flowering plants including Oryza sp., Arabidopsis, Zea mays, Nicitiana tabacum, and pumpkin are composed of a multigene family (Scandalios 1990;Frugoli et al 1996;Guan and Scandalios 1996;Iwamoto et al 2000; reviewed by Mhamdi et al 2010;Liu et al 2015). Multiple forms of CATs in plants are usually expressed in different tissues and at their developmental stages (reviewed by Scandalios et al 1997).…”
Section: Catalase Genomic Characterization Genes and Isoformsmentioning
confidence: 99%
“…They are recognised as essential defence enzymes against ROS-induced oxidative stress [154,155]. In addition, they are involved in plant defence and metabolism as well as the perception of cellular signals [156].…”
Section: •−mentioning
confidence: 99%